PENGARUH RESIKO INVESTASI TERHADAP MINAT MASYARAKAT BERINVESTASI SUKUK DI BANK SYARIAH MANDIRI BATURAJA - Epriyanti Epriyanti (Jurnal Manajemen Bisnis Unbara, 2020)
The problem in this research is whether there is influence of investment risks against society’s interest in investing in sukuk at PT. Bank Syariah Mandiri Baturaja. The population in thisresearch is a society which performs investment sukuk at PT. Bank Syariah Mandiri Baturaja. The population in this research is the 184 people, samples obtained as many as 65 people. From research conducted by the author can be drawn the conclusion that the influence of investment risks against society’s interest in investing in sukuk at PT. Bank syariah Mandiri Baturaja.The formula that is used in this research is a simple linear regression, from the study stated that the investment risk to the community’s interest in investing in sukuk,the value t hitung is greater that t tables, and R square 87,2%. It mean 87,2% of community interest in investing in sukuk influence by investment risks.